The Correlations of Knowledge and Mother’s Visit Compliance with Growth Trends of Children Under Five Post Pandemic at Integrated Service Post Program in Sidoarjo District - Karina Dinar Ayunda; Annas Buanasita; Ani Intiyati; Nurul Hindaryani (Journal of Nutrition Explorations, 2023)
Growth trends of children under five are affected by several factors including mother’s knowledge and mother’s visit compliance to Integrated Service Post Program. During the COVID-19 pandemic mother’s visit to Integrated Service Post Program decreased, so this study to analyse the corrrelations of mother’s knowledge and mother’s visit compliance with growth trends of children under five post pandemics at Integrated Service Post Program in Sidoarjo District. The sample of 49 children under five. Collected data through interviews and observing growth chart to see growth trends. In this study, the average age of mothers under five was 31 years old, had a Diploma/Bachelor degree, had less knowledge, had a good level of visit compliance to Integrated Service Post Program, but most of the growth trends of childrens under five are not matched. The study shows that there is relationship between knowledge and mother’s visit compliance to the Integrated Service Post Program with the post-pandemic growth trend of children under five. Therefore, it is hoped that Integrated Service Post Program cadres can educate mothers under five about the importance of Integrated Service Post Program and mother can learn about how to read growth trends of children under five.